Simulation for Procedural Planning and Intracardiac Echo for Enhancing Precision in Cardiac Interventions With a Focus on Left Atrial Appendage Closure - Jaya Chandrasekhar, MBBS, MS, PhD; Jacqueline Saw, MD (Structural Heart)
In recent years, structural interventions have explored three-dimensional printing and computer simulation technologies to facilitate optimal device selections for more efficient procedures with fewer patient complications. Cardiovascular procedures, both structural interventions and electrophysiological procedures, have examined the utility of intracardiac echocardiography. In this review, we will discuss the growth of these technologies and highlight recent studies with a key focus on left atrial appendage closure.